The Integrated Assessment of Land Degradation - Luca Salvati; Maria Elisa Venezian Scarascia; Marco Zitti; Agostino Ferrara; Valentina Urbano; Maurizio Sciortino; Carlo Giupponi (Italian Journal of Agronomy)
This paper reviews recent findings on the complex field of land degradation (LD) with focus on the Mediterranean Basin and Italy, in particular. The LD definition and assessment methods are examined in the light of the most important natural and human driving forces of the phenomenon, such as land use and climate changes.Various methodological issues are dealt with from multidisciplinary perspective with the aim of providing the ground for the development of integrated approaches: monitoring needs, assessment of costs, development of mitigation strategies, etc. Factors affecting land vulnerability to degradation are classified into bio-physical and socio-economic drivers with some examples of applications in Italy. The role of determinants such as agricultural development, population growth, and urban sprawl is recognised as important but still ambiguous and thus needs further studies. Based on these findings, policy responses aimed at mitigating LD and thus reducing desertification risk are discussed and methodological proposal are presented.